(untitled) (The Review of Diabetic Studies, 2024)
One of the main issues faced by the healthcare sector is still the inability to avoid hospital readmissions. Additionally, these readmissions are a drain on resources, negatively influencing patient health and signaling the inadequacy of transitional care. Nurse-led solutions in the form of structured discharge planning, home follow-up visits, and telemonitoring have been recognized as the most effective to overcome these hurdles, however, just a few studies have assessed their joint impact through quasi-experimental methods. Thus, the current study aims to examine the effectiveness of a nurse-led transitional care program. It is specifically looking at how these nurses can help reduce the 30-day all-cause hospital readmissions of older patients with chronic medical conditions. The plan was to carry out a quasi-experimental design where the one group received the nurse-led discharge planning, home visits, and telemonitoring, while the other group just got standard care for comparison. The data analysis encompassed various statistical procedures including descriptive statistics, chi-square tests, independent-samples t-tests, and multivariate regression. The intervention of nurses had a significant effect in lowering readmission rates along with the improvement of patient satisfaction, self-management skills, and health-related quality of life. The findings validate the necessity of a nursing workforce that continually enhances care and prove the efficacy of the multipurpose transitional care models in avoiding hospitalizations that could have been prevented. Thus, the study has drawn out some of the most important implications in the areas of clinical practice, healthcare policy, and future research.